2018
DOI: 10.1140/epjc/s10052-018-5601-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Hamiltonian formulations and stability of higher-derivative extensions of 3d Chern–Simons

Abstract: Most general third-order 3d linear gauge vector field theory is considered. The field equations involve, besides the mass, two dimensionless constant parameters. The theory admits two-parameter series of conserved tensors with the canonical energy-momentum being a particular representative of the series. For a certain range of the model parameters, the series of conserved tensors include bounded quantities. This makes the dynamics classically stable, though the canonical energy is unbounded in all the instance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…Equation (19) coincides with the definition (16) of the conjugate momenta p i . Equation (20) can be rewritten as…”
Section: Passage To Canonical Hamiltonian Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (19) coincides with the definition (16) of the conjugate momenta p i . Equation (20) can be rewritten as…”
Section: Passage To Canonical Hamiltonian Formulationmentioning
confidence: 99%
“…To gain a better understanding of the constraints and the elimination of instabilities, we consider two simple examples of harmonic oscillator systems in more detail. Contrary to previous work [17][18][19][20], which exploits the existence of multiple, inequivalent Hamiltonian structures in linear systems (mainly Pais-Uhlenbeck oscillators) to switch to Hamiltonians bounded from below, we here keep unbounded Hamiltonians, like in the Ostrogradsky approach, but on a larger space.…”
Section: Examples: Harmonic Oscillatorsmentioning
confidence: 99%
“…been recently found that the model is multi-Hamiltonian at free level [21]. To the best of our knowledge, it is the first known explicit example of higher derivative field theory that admits multi-Hamiltonian structure.…”
mentioning
confidence: 91%
“…The canonical Ostrogradski Hamiltonian is included in the series. The series of non-canonical Hamiltonian formulations was constructed explicitly in [11,12] for the extended Chern-Simons theory [13] of the third and fourth order.…”
Section: Introductionmentioning
confidence: 99%
“…The canonical Ostrogradski Hamiltonian is included in the series. The series of non-canonical Hamiltonian formulations was constructed explicitly in [11,12] for the extended Chern-Simons theory [13] of the third and fourth order.In the present work, we consider the Hamiltonian formulation for the extended Chern-Simons of arbitrary finite order. At free level, the theory of order n admits (n − 1)-parametric series of Hamiltonian formulations with Hamiltonian being the 00-component of any conserved tensor from the series [14].…”
mentioning
confidence: 99%